THE ROLE OF DIALECTS IN EFL STUDENTS’ PRONUNCIATION AT UNIVERSITY - Siti Anisa Femi Amalia; Evi Rosmiyati; Amiruddin (Esteem Journal of English Education Study Programme, 2024)
The purpose of this study is to examine how dialect affects how English as a Foreign Language (EFL) students at Pgri University of Palembang pronounce the language. In the fourth semester of the 2023–2024 academic year, a total of 16 students from Palembang, Musi Banyuasin, Ogan Ilir, and Pagaralam participated in the study. The investigators utilized interviews and questionnaires as well as descriptive qualitative research approaches to obtain data. Twelve students agreed, according to the questionnaire results, that their dialect influences how they pronounce English words. Furthermore, the findings of the interviews revealed that the students hailing from Pagaralam, Ogan Ilir, and Musi Banyuasin believed their dialect contributed to a distinct pronunciation. In summary, dialect plays a part in how university students who are learning English as a foreign language pronounce the language.